Effect of Thymol Addition and Withdrawal on Some Blood Parameters, Antioxidative Defence System and Fatty Acid Profile in Rabbit Muscle - Kristina Bacova; Karin Zitterl-Eglseer; Lubica Chrastinova; Andrea Laukova; Michaela Madarova; Sona Gancarcikova; Drahomira Sopkova; Zuzana Andrejcakova; Iveta Placha (Animals, 2020)
Thymol concentrations in rabbit plasma, intestinal wall (IW) and faeces were detected, and the effects of thymol application and withdrawal on biochemical, antioxidant parameters and fatty acids (FA) in blood (B) and muscle (M) were studied. Forty-eight rabbits were divided into two experimental groups (control, C and with thymol 250-mg/kg feed, T). Thymol was administered for 21 days (TA) and withdrawn for seven days (TW). Thymol in plasma correlated with that in the IW (Spearman′s correlation coefficient (rs) = −1.000, p = 0.0167, TA) and was detected in faeces (TA and TW). In TA alkaline phosphatase (p = 0.0183), cholesterol (p = 0.0228), malondialdehyde (p = 0.003), glutathione peroxidase (p = 0.0177) in B and lactate dehydrogenase (M, p = 0.0411) decreased; monounsaturated FA (p = 0.0104) and α-linolenic acid (p = 0.0227) in M increased. In TW urea (p = 0.0079), docosapentaenoic acid (p = 0.0069) in M increased; linoleic acid (p = 0.0070), ∑ n−6 (p = 0.0007) in M and triglycerides decreased (B, p = 0.0317). In TA and TW, the total protein (p = 0.0025 and 0.0079), creatinine (B; p = 0.0357 and 0.0159) and oleic acid (M; p = 0.0104 and 0.0006) increased. Thymol was efficiently absorbed from the intestine and demonstrated its biological activity in blood and the muscles.